Preservare l’incontro con i beni culturali: una dialettica tra digitale e umanesimo in epoca Covid-19 - Steven Stergar (Ricerche di S/Confine, 2020)
Let’s try to force ourselves for a moment imagining the world as we know it but deprived of its beauties guarded and preserved by the cultural sector. Let’s imagine now a world devoid of figurative arts, verses in prose and poetry, moving images and music. The current pandemic caused by Covid-19 seems to be able to – partially – represents a scenario of this kind. The months of lockdown have in fact put the cultural sector to the test, forcing operators to reinvent, where possible of course, forms of involvement that would allow the encounter with cultural heritage. But nevertheless, these were also months in which many people were able to enjoy arts and products while remaining duly closed at home. Today’s media tools allow us to reinvent new forms of involvement (whether in presence or remotely), favoring those “shocks” (Bellour, 2009) that arise from encounters between the subject and the artworks; today, cognitive neurosciences recognizes these encounters as events in which both mind and body are strongly connected each other (Damasio, 2008; Gallese & Guerra, 2015). And yet, how can we guarantee these encounters and bodily phenomena between the subject and the artworks in a period in which distancing has become a social norm? The cultural sector responds to the challenge by proposing a series of strategies that increasingly bring into play a dialectic between humanist tradition and digital culture, creating projects capable of stimulating people to get closer to artworks, respecting at the same time the rules necessary today to safeguard everyone. Among these, the expansion of the perceptual and experiential potentialities proposed by the DRAMSAM – Giuliano Center for Ancient Music becomes one of the many original examples of significant interest for us.